RELATIONSHIP BETWEEN GOVERNMENT POLICIES AND KNOWLEDGE MANAGEMENT (KM) IN KNOWLEDGE BASED AND HIGH-TECH FIRMS - Vahid Ghorbani , Abolhassan Fagihi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The present paper examines the relationship between government policies and knowledge management in knowledge-based and high technology firms and evaluates government policies within them. This is a descriptive research in terms of strategy and purpose, fundamental in terms of audience, and cross-sectional in terms of time. The statistical population included 51 expert managers of 7 knowledge-based and high-tech firms. The data was gathered by probabilistic (qualitative) judgment and availability sampling. Finally, government support policies in the areas of knowledge transfer, knowledge sharing, architecture, networking, and guidance were explored and the successful policies as well as those which fail to meet the expectations of knowledge-based and high-tech companies were determined. In addition, criticisms against the government’s performance and suggestions for more successful implementation of the policies were presented according to science and technology policies. The findings show that high-tech firms gain diverse government support, mostly in dimensions of financial and tax incentives, organizational architecture, knowledge transfer and guidance, and to a lesser extent in the dimensions of networking and sharing knowledge. The researcher contributed to add to the fundamental knowledge of government support policies in firms with high Iranian technology. The researcher also tested the hypotheses that make a connection between the type of government support policies and the need for knowledge management in high-tech firms.